OLADE's energy efficiency programs : contribution to the sustainable development of Latin America and the Caribbean (1999)
Highlights two of OLADE's projects in efficient use of energy viz. the PIER Central and PIER Andean project.
Keywords: ENERGY EFFICIENCY